2018
DOI: 10.1039/c7sc04736c
|View full text |Cite
|
Sign up to set email alerts
|

Unusual mechanisms in Claisen rearrangements: an ionic fragmentation leading to a meta-selective rearrangement

Abstract: A mechanistic investigation of the acid-catalysed redox-neutral arylation of ynamides intertwining ESI-MS, DFT and experiments reveals diverse pathways available from an otherwise simple-looking transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Computational analysis revealed the new product to arise from an initial [3,3]-sigmatropic rearrangement onto the substituted ortho -carbon atom and a subsequent 1,2-alkyl shift, followed by rearomatization (Scheme 34c). 126…”
Section: Sulfoxidesmentioning
confidence: 99%
“…Computational analysis revealed the new product to arise from an initial [3,3]-sigmatropic rearrangement onto the substituted ortho -carbon atom and a subsequent 1,2-alkyl shift, followed by rearomatization (Scheme 34c). 126…”
Section: Sulfoxidesmentioning
confidence: 99%
“…In fact, the versatility of silane 26 is illustrated by the synthesis of the structurally diverse series 28 – 32 (Table A). For the ortho, ortho’ ‐disubstituted λ 3 ‐aryliodanes, the incoming group is redirected to the meta C−H position (product 33 ), in line with a [3,3]‐rearrangement followed by an ortho ‐to‐ meta [1,2]‐shift . As seen in Table B, the open‐chain sulfonylated allylsilane 34 was also reactive, providing the corresponding ortho coupling product 35 in 92 % yield.…”
Section: Methodsmentioning
confidence: 98%
“…Recently, Maulide has reported that this kind of rearrangement is on the borderline between concerted and stepwise mechanisms. [9] However, research focusing on the nature of the charge-accelerated sigmatropic rearrangement of arylsulfonium species remains limited.…”
Section: Introductionmentioning
confidence: 99%